A multicentre longitudinal observational study of changes in self reported health status in people with Parkinson's disease left untreated at diagnosis. Issue 5 (10th November 2006) - Grosset, D; Taurah, L; Burn, D J; MacMahon, D; Forbes, A; Turner, K; Bowron, A; Walker, R; Findley, L; Foster, O; Patel, K; Clough, C; et al.
Abstract : Background: The issue of when to start treatment in Parkinson's disease (PD) remains controversial. Some favour treatment at diagnosis while others opt for a "wait and watch" policy. The effect of the latter policy on the self reported health status of people with PD is unknown. Aims: To record self reported health status through longitudinal use of a validated PD specific questionnaire (PDQ-39) in untreated PD patients in multiple centres in the UK. To compare patients who were left untreated with those who were offered treatment during follow-up. Methods: A multicentre, prospective, "real life" observational audit based study addressing patient reported outcomes in relation to self reported health status and other sociodemographic details. Results: 198 untreated PD were assessed over a mean period of 18 months. During two follow-up assessments, the self reported health status scores in all eight domains of the PDQ-39 and the overall PDQ-39 summary index worsened significantly (p<0.01) in patients left untreated. In a comparative group in whom treatment was initiated at or soon after diagnosis, there was a trend towards improvement in self reported health status scores after treatment was started. Conclusions: This study addresses for the first time self reported health status, an indicator of health related quality of life, in untreated PD. The findings may strengthen the call for re-evaluation of the policy to delay treatment in newly diagnosed patients with PD.